DEAD MAN'S WIRE - Kolodney, Austin; Skarsgård, Bill; Montgomery, Dacre, 1994-; Elwes, Cary, 1962-; Herrold, Myha'la, 1996- (Row K Entertainment, 2026)
Dead Man's Wire is the fascinating true story of the 1977 kidnapping that turned aspiring Indianapolis entrepreneur Tony Kiritsis into an eccentric outlaw folk hero, directed by Academy Award-nominated filmmaker Gus Van Sant.